DIGITALIZATION AND USING OF FINANCIAL RESOURCES OF THE COMPANY (by the example of Air Astana JSC) - Касенова, Г.; Садвакасова, К. (Journal of Economic Research & Business Administration, 2019)
The article is devoted to the actual problem of the method of analyzing the state, security and efficiency of the use of financial resources of an enterprise under digitalization conditions. The article provides a classification of indicators characterizing the state and efficiency of using own and borrowed funds, the method of their definition and use in economic analysis. The purpose of the article is to analyze the factors influencing the development of resources, as well as the sources of financial resources of entrepreneurs. The scientific and practical significance of the work is due to the fact that at the moment enterprises are forced to pay more attention to the problems associated with the formation and improvement of the efficiency of their financial resources and to intensify the search for ways to improve their financial condition. In the research methodology, the principle of comprehensive analysis of indicators was chosen, which comprehensively characterize the efficiency of the formation and use of financial resources. Summing up the main results, analysis and conclusions of the research work, it should be emphasized that the digitization of financial resources in an enterprise, which is the basis for ensuring its financial sustainability, will help to create all possibilities for further financial and economic activity with positive results. The theoretical and practical significance of the study lies in the fact that its conclusions and suggestions can be used in the formulation of the task of analysis and planning and the development of appropriate software by specialists of financial management companies, as well as in the educational process in preparing and lecturing for students of the specialty «Finance».